Spatiotemporal Changes of Near-Surface Ozone Concentration From 2015 to 2018 in Beijing - Xie, Junfei; Shi, Shengwei; Wu, Lingyun; Zhang, Xin (Frontiers in Environmental Science, 2021)
In this study, we investigated the spatiotemporal changes of surface O3 concentration by using the measurements of O3 concentration from 35 automatic air quality monitoring stations in 2015 and 2018. The results showed that: (1) The diurnal variation in the atmospheric O3 concentration at 35 monitoring stations showed a single-peak mode, which had a minimum concentration from 06:00 to 07:00, and reached a maximum from 14:00 to 15:00, and then declined. The O3 concentration was significantly positively correlated with the air temperature, total solar radiation, and wind speed, while O3 concentration was negatively correlated with the relative humidity. (2) The annual variation in the O3 concentration tended to be a "bell-shaped" curve distribution with a peak in the summer from June to August and the lowest value in the winter from December to January. The seasonal variation in the O3 concentration had a large variability among the different stations. (3) The annual average of the surface O3 concentration at 35 stations in Beijing was 57.5 ± 9.8 gm-3 in 2015 and 60.3 ± 9.0 gm-3 in 2018. The annual average of the atmospheric O3 concentration was lowest at the Dong sihuan Station (42.4 gm-3) and highest at the Miyun Reservoir Monitoring Station (85.5 gm-3) in Northeastern Beijing. The spatial pattern of the atmospheric O3 concentration can be explained by the traffic pollution, vegetation coverage, atmospheric regional transmission, and atmospheric particulate matter concentration. (4) The spatial pattern of the atmospheric O3 in 2015 and 2018 also showed lower concentrations in the Central and Southern districts, and higher concentrations in the Northern districts in Beijing. The average annual concentration of atmospheric O3 in the Northeastern region with good vegetation coverage was the highest.